Data‐driven methodology to realize strong and broadband microwave absorption properties of polymer‐fly ash cenosphere composite. Issue 16 (3rd December 2021) - Bora, Pritom J.; Mahanta, Bibhusita; Kishore,; Ramamurthy, Praveen C.
Abstract: A very efficient microwave absorption characteristic of conducting polymer (polyaniline or PANI) incorporated fly ash cenosphere (FAC), which is a waste of thermal power plant, is revealed in this work with materials data‐driven approach. The different loading (wt%) of PANI‐FAC hybrids to a polymer such as polyvinyl butyral (PVB) results in different reflection loss (RL). However, RL performances do not improve by simply increasing the PANI‐FAC hybrid loading (wt%) to PVB. Herein, PANI‐FAC loading to PVB is optimized through the electromagnetic data‐driven methodology. A remarkable RL ≤ − 40 dB with entire X‐band (8.2–12.4 GHz) absorption bandwidth (RL ≤ −10 dB, RL value −10 dB corresponds to 90% absorption) is predicted for 8.5 wt% PANI‐FAC hybrid loaded PVB‐PANI‐FAC composite. The predicted RL matched with experimental data (minimum RL value −44.5 dB with X‐band absorption bandwidth), confirming the proposed proof of concept of data‐driven methodology to obtain broadband and robust microwave absorption characteristics of polymer‐FAC composites. Abstract :